Adición de orégano (Origanum vulgare L) deshidratado en alimentación de pollos COBB 500 y su efecto en parámetros productivos y sanguíneos - Argandoña Moreira, Marlon Asbel (2023)
In order to evaluate the effect of adding dried oregano (Origanum vulgare) on health and production parameters in chickens of the Cobb 500 genetic line, this research was carried out at the Bovine Herd Teaching, Research and Linkage Unit at ESPAM "MFL", a completely randomized block design (DCA) was used, in which treatments based on dehydrated oregano (OD) were used in three doses (300, 400 and 500 ppm) and a control treatment with promoter antibiotic of growth (APC) bacitracin 250 ppm, where the assumptions of Shapiro-Wilk normality and homogeneity of variances with the Fisher test (0.05) were executed, the present assumptions were not met, so the Kruskal Wallis test was used and the separated the medians in pairs, using the InfoStat 2021 statistical software, and it turned out that the treatment with OD at 400 ppm in females and in males obtained a highly significant difference (p<0.001), which demonstrated that this improves the productive indices (gain of weight, feed conversion and carcass yield) and did not have consequences of abnormal variation in hematological levels, therefore they did not cause negative effects on health, in addition they did not generate pharmacological residues and did not cause bacterial resistance, consequently, this product is an alternative that can efficiently replace antibiotic growth promoters that increases profitability in relation to cost benefit.